1976
DOI: 10.1029/jc081i036p06441
|View full text |Cite
|
Sign up to set email alerts
|

Long-period waves on a natural beach

Abstract: A field experiment is described in which three two‐component electromagnetic flowmeters were used to measure simultaneously the longshore (υ) and onshore‐offshore (u) velocity components along a line normal to the shoreline and up to 100 m offshore. Spectral analysis of the data from this experiment reveals the presence of a set of discrete spectral peaks of low frequency (0.014–0.05 Hz) which dominate over the wind wave peak close to the shoreline and which decay in amplitude with distance from the shore. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 19 publications
2
77
0
Order By: Relevance
“…Short-wave swash derives from locally-generated wind waves and swell (e.g., Waddell, 1976;Hughes, 1992;Holland and Puleo, 2001), whereas long-wave swash (or infragravity swash) includes leaky-mode standing waves and edge waves (e.g., Huntley, 1976;Aagaard, 1991;Holland et al, 1995;Holland and Holman, 1999). A fundamental difference between incident short-waves and surf zone long-waves is that the former usually break before reaching the beach face whereas the latter typically do not.…”
Section: General Conceptsmentioning
confidence: 99%
“…Short-wave swash derives from locally-generated wind waves and swell (e.g., Waddell, 1976;Hughes, 1992;Holland and Puleo, 2001), whereas long-wave swash (or infragravity swash) includes leaky-mode standing waves and edge waves (e.g., Huntley, 1976;Aagaard, 1991;Holland et al, 1995;Holland and Holman, 1999). A fundamental difference between incident short-waves and surf zone long-waves is that the former usually break before reaching the beach face whereas the latter typically do not.…”
Section: General Conceptsmentioning
confidence: 99%
“…T m01,lo is affected by the frequency distribution of the infragravity energy density, and is therefore sensitive to the nodal structure of the standing infragravity waves (e.g. Suhayda, 1974;Huntley, 1976;Holman, 1981;Guza and Thornton, 1985, and others). As such, it is expected to vary in the cross-shore.…”
Section: Ajh Reniers Et Al / Coastal Engineering XX (2005) Xxx -Xxxmentioning
confidence: 99%
“…infragravity waves that radiate away from the surfzone, and trapped long waves (edge waves) that cannot escape from the shoreline due to strong refraction. Previous measurements (Suhayda, 1974;Huntley, 1976;Holman, 1981;Wright et al, 1982;Guza and Thornton, 1985, among others) have shown the increased contribution of infragravity motions to the total gravity wave spectrum with decreasing water depth. This effect is associated with the wave-breaking induced saturation of the incident waves, whereas the infragravity waves continue to shoal without breaking, consequently their relative contribution increases rapidly as the shoreline is approached and can reach energy levels significantly higher than the incident wind waves (Wright et al, 1982;Guza and Thornton, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holman and Bowen (1982) proposed a model that incorporated low frequency, edge wave motions, and demonstrated theoretically that the bottom drift patterns associated with complex wave fields looked similar to many commonly observed nearshore topographic features. There can be little doubt as to the existence of edge waves (e.g., Huntley, 1976;Huntley et al, 1981;Katoh, 1981;Oltman-Shay and Guza, 1987), and Bowen and Huntley (1984) point out that there is ample evidence to suggest that "low-frequency motions are dominant over a significant region in the surf zone 0025-3227/90/$03.50 8.0. BAUER AND B. GREENWOOD and that this dominance increases in very severe conditions, precisely the conditions in which the most active sediment transport is expected to occur.…”
Section: Introductionmentioning
confidence: 99%